A unified energy flow analysis considering initial guesses in complex multi-energy carrier systems. (15th December 2020) - Sun, Qiuye; Dong, Qianyu; You, Shi; Li, Zhibo; Wang, Rui
Abstract: Multi-energy flow (MEF) analysis is the most fundamental issue in studying multi-energy carrier (MEC) systems. In the tight coupling MEC systems, the unified energy flow analysis is indispensable to tackle the problems of accuracy and in decomposition. Therefore, on the basis of the comprehensive node classification and modified Jacobian matrix, this paper proposes a unified energy flow analysis approach with Newton method considering initial guesses selection for complex MEC systems including electrical, gas, heating sub-networks. This approach is based on the presented convergence theorem, which can determine in advance whether the initialization can converge to results, since the Newton method, the main approach of the unified energy flow analysis, is sensitive to its initial guesses selection. Once the initialization can not converge, the proposed approach can help selecting proper initial guesses for Newton method to guarantee the convergence of the unified energy flow. Several cases are studied to demonstrate the effectiveness and applicability of the proposed approach on judging and choosing initialization for the unified energy flow analysis. Highlights: A unified energy flow analysis approach is proposed for multi-energy carrier systems. The convergence theorem for Newton-Raphson solving energy flow is proposed. The comprehensive node classification and several novel slack types are presented. The more realistic heating Jacobian matrix is utilized. Different scales of multi-energy carrier systems are considered.